Nanocomposites - Recent Evolutions 2019
DOI: 10.5772/intechopen.81329
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Nanocomposites with Different Types of Nanofiller

Abstract: The development of polymer nanocomposites has been an area of high scientific and industrial interest in the recent years, due to several improvements achieved in these materials, as a result of the combination of a polymeric matrix and, usually, an inorganic nanomaterial. The improved performance of those materials can include mechanical strength, toughness and stiffness, electrical and thermal conductivity, superior flame retardancy and higher barrier to moisture and gases. Nanocomposites can also show uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 108 publications
2
94
0
4
Order By: Relevance
“…It can be suggested that better UHMWPE-CNF adhesion was achieved through melt blending as compared to ethanol mixing. This is supported by published report stating that infiltration of melt polymer with addition of shear force during melt blending could results in smaller filler agglomerates and better interaction [48]. The information on toughness could also be obtained from the area under the stressstrain curve in Figure 2.…”
Section: Mechanical Propertiessupporting
confidence: 71%
“…It can be suggested that better UHMWPE-CNF adhesion was achieved through melt blending as compared to ethanol mixing. This is supported by published report stating that infiltration of melt polymer with addition of shear force during melt blending could results in smaller filler agglomerates and better interaction [48]. The information on toughness could also be obtained from the area under the stressstrain curve in Figure 2.…”
Section: Mechanical Propertiessupporting
confidence: 71%
“…The rotational speed relates to the shear stress of polymer; increasing shear stress promotes polymer melt infiltration into filler agglomerates. This weakens agglomerates packing and structure, resulting in smaller agglomerates and better dispersion [ 52 ]. However, the effects of shear stress and melt infiltration on filler’s dispersion primarily depend on the melt viscosity of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…; in all cases, the aim is to generate three-dimensional networks interconnected to facilitate the passage of electrons or phonons, to generate an electro/thermo-conductive material. [21,22].…”
Section: Polymeric Nanocompositesmentioning
confidence: 99%